The Role of Religion as Environmental Ethics: An Ecotheological Perspective on the Ecological Crisis among Muslim Communities in Central Kalimantan - Rani, Rani; Rahmawati, Siti; Surawan, Surawan (Jurnal Studi Agama, 2025)
Environmental crises, such as forest and land fires (karhutla) in Central Kalimantan, pose severe ecological, social, and economic threats, demanding immediate and context-sensitive ethical responses. This study asserts that religion, particularly Islamic ecotheology, plays a critical role in shaping environmental ethics and guiding sustainable practices among Muslim communities. Using a qualitative approach through literature review and media document analysis (2019–2025), the study explores how Islamic teachings can be applied to address these ecological challenges. The findings reveal three main points. First, Islamic environmental ethics highlight human responsibility as khalifah (stewards of the earth) to maintain mizan (balance) and pursue maṣlaḥah (public good), yet these values are not fully reflected in community practices, as land burning persists. Second, Islamic ecotheology has been promoted through fatwas, organizational movements, and eco-education programs, though its impact is limited without strong law enforcement and community participation. Third, integrating Islamic principles with Dayak local wisdom and collaborative governance enhances practical solutions for fire prevention and ecological stewardship. Overall, Islamic ecotheology offers both normative guidance and actionable frameworks, emphasizing the synergy of religion, culture, and policy in mitigating environmental crises in Central Kalimantan.